"How to Taste a Festival". Ekphrasis and Sensoriality around Urban Celebrations during the Early Modern Period. - González-Román, María del Carmen (My University, 2023)
The main title of this work: "How to Taste a Festival" is inspired by the seminal and indispensable study by Victor Stoichita originally entitled: "How to Taste a Painting" (2010). In that essay, the prestigious art historian studies Titian's painting The Worship of Venus (1518) and argues that the detailed and vivid description made by Philostratus, which served as inspiration for the famous Venetian painter, demonstrated the ability to recreate, from words and sounds, all the sensations that the original painting could express. Stoichita thus points to the multisensory nature of the description of a painting, a description that attempted to activate not only sight and hearing but also the senses of smell, taste and touch. Halfway between literature and visual culture are the texts that describe the festivities and celebrations that took place throughout the Early Modern period, known as festival books. This research focuses on the multisensory aspects of urban festivities contained in this type of narration, where the effects and affects aroused by the celebration are conveyed through the description of visual, olfactory, sound, tactile and gustatory resources. From this point of view, another way of approaching the knowledge of urban reality in a festive context is proposed. To taste an urban festival, not so much, or not only, in terms of the sense of taste, as in terms of the third meaning of the term "savour" in the Spanish Dictionary: "To appreciate carefully and with delight a pleasing thing".
Keywords: Fiestas populares - S. XV-XVI; Libros ilustrados - S. XV-XVI; Sentidos en el arte; Sensoriality; Ekphrasi; Scenographic Culture; Scenographic culture; Festival books